Transformasi Pasar Bambu Kuning: Dari Pasar Tradisional menuju Sentra Ekonomi Perkotaan, 1974-2010 - Susanti, Desi; Ramadhan, Fauzan Syahru; Nugroho, Khairana Zata (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2025)
This article examines the transformation of Pasar Bambu Kuning, a traditional market in Bandar Lampung, Indonesia, from its establishment during the colonial Dutch East Indies period to its transformation into an urban economic center in 2010. Using historical methods such as heuristics, criticism, interpretation, and historiography, this article draws on primary sources such as local and national newspapers, colonial-era visual sources, and secondary sources including scholarly articles, research reports, books, and unpublished theses. The findings of this study reveal that Pasar Bambu Kuning evolved from a colonial periodic market into a vital permanent trading center after Indonesia’s independence, driven by population growth and commercial needs. This transformation included major renovations between 1974 and 1990, resulting in a three-story building structure, although the process was marked by conflicts and disputes among the stakeholders. This study contributes significantly to the understanding of the historical transformation of traditional markets in Indonesia and their role in shaping urban economies and societies. It serves as a valuable historical reference for future studies on urban development and the revitalization of traditional markets.